Is Russian Energy Policy towards the EU Only about Geopolitics? The Case of the Third Liberalisation Package. Issue 4 (1st October 2016) - Romanova, Tatiana
ABSTRACT: Russian external energy policy is frequently described as geopolitical (as opposed to EU energy policy, which is often characterised as market-based). This article reviews geopolitical and market approaches in existing studies and identifies paradigmatic and instrumental levels in each of them. It then proceeds to demonstrate that although the geopolitical paradigm dominates in Russia, Russia has also reacted to the EU's third liberalisation package, using legal and technocratic instruments, which are parts of the market approach. Each set of instruments has its institutional basis in Russia: the President, the Ministry of Foreign Affairs (MFA) and Gazprom work in geopolitical ways but with frequent recourse to legal instruments, the Ministry of Economic Development (MED) promotes legal instruments and the Ministry of Energy (ME) is the centre of the technocratic activities, which Gazprom also frequently applies at present. This study therefore provides a more complex picture of Russian external energy policy. Moreover, it reveals a potential opening for a degree of policy convergence between the EU and Russia. In this context it is regrettable that legal and technocratic instruments were compromised as a result of the 2014 worsening in EU-Russian relations.